(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The general characteristics and the emergence of probationary supervision in criminal proceedings are investigated. The versatility of such a phenomenon as probation is considered, which determines the plurality of scientific approaches to understanding its essence from the point of view of criminal law in the form of a measure of criminal law enforcement; penitentiary enforcement of probation supervision and control over persons conditionally early released from imprisonment and determined by the court of a correctional term for the period of probation supervision and from the point of view of criminal procedure law.